1982
DOI: 10.1136/sti.58.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobes in men with urethritis

Abstract: SUMMARY Sixty-four men with non-gonococcal urethritis (NGU), seven with gonococcal urethritis (GU), and 30 who had no symptoms or signs of urethritis were studied. Chlarnydia trachomatis was isolated from urethral specimens taken from 22% of the men with NGU, and 1 8/o with GU, but not from those who did not have urethritis even though 20 (67%) of them had a history of NGU, GU, or both. The chlamydial isolation rate for men having NGU for the first time was 30%7o. Ureaplasma urealyticum was isolated from 42% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…We found similar anaerobic isolation rates as previously reported [2,8], Peptostreptococcus spp. being the most frequent isolate [2,8,9,1 I].…”
Section: Discussionsupporting
confidence: 91%
“…We found similar anaerobic isolation rates as previously reported [2,8], Peptostreptococcus spp. being the most frequent isolate [2,8,9,1 I].…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge of the contribution of the blackpigmented Gram-negative anaerobic bacilli to the normal flora of the genito-urinary tract is essen-224 tial for understanding the pathological processes. In men, anaerobic Gram-positive cocci [2] are a major part of the normal urethral flora but the Gram-negative Bacteroides, Prevotella and Porphyromonas are not generally found, although there is some evidence that "Bacteroides" ureolyticus is a normal urethral resident [3].…”
Section: Normal Floramentioning
confidence: 99%
“…Other infectious agents may have a role in th6 35-67.5 % of cases with an unexplained aetiology. Fontaine et al (5) suggested that an anaerobic gram negative bacillus, later identified as Bacteroides ureolyticus (6), might play a role in NGU and called it an NGU-associated anaerobe. It was isolated from 50 % of men with NGU attending a venereal disease clinic, but from only 13 % of men without NGU.…”
mentioning
confidence: 99%